At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Use the zero product property to find the solutions to the equation x2 + 12 = 7x.
x = –4 or x = 3
x = –4 or x = –3
x = –3 or x = 4
x = 3 or x = 4


Sagot :

Answer:

In a product like:

a*b = 0

says that one of the two terms (or both) must be zero.

Here we have our equation:

x^2 + 12 = 7x

x^2 + 12 - 7x = 0

Let's try to find an equation like:

(x - a)*(x - b) such that:

(x - a)*(x - b)  = x^2 + 12 - 7x

we get:

x^2 - a*x - b*x  -a*-b = x^2 - 7x + 12

subtracting x^2 in both sides we get:

-(a + b)*x + a*b = -7x + 12

from this, we must have:

-(a + b) = -7

a*b = 12

from the first one, we can see that both a and b must be positive.

Then we only care for the option with positive values, which is x =3 or x = 4

replacing these in both equations, we get:

-(3 + 4) = -7

3*4 = 12

Both of these equations are true, then we can write our quadratic equation as:

(x - 3)*(x - 4) = x^2 + 12 - 7x

The correct option is the last one.

Answer:

d

Step-by-step explanation:

Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.